PERENCANAAN STRATEGIS SISTEM INFORMASI PADA MCDONALD'S MENGGUNAKAN METODE WARD AND PEPPARD - Alif Millati Putri (JURNAL TEKNOLOGIA, 2021)
The more stringent the industrial world, each industry must formulate a strategic plan so that the policies taken are effective and efficient, strategic planning in the IS/IT sector has a major influence on the success of a company, if the strategy taken is wrong it will be very detrimental to the company, one of the methodologies used is that can be used to formulate IS/IT strategies is the methodology introduced by ward & peppard, where in this methodology there are steps that can be taken to formulate IS/IT strategic planning, before formulating IS/IT strategic planning, some analysis must be carried out including internal and external business analysis as well as internal and external IS/IT analysis then the analysis results can be described and finally processed to formulate IS/IT strategies, then the formulation will create application roadmaps and application portfolios in the future. This American gourmet restaurant was founded by brothers Richard and Morris 75 years ago, in 1940. McDonald's first stall was a barbeque shop in San Bernardino, California. Changes in the environment is a situation that is difficult to predict, predict and guarantee the future. Changes that have a negative impact are an obstacle for the industry, on the contrary changes that have a positive impact will support the continuity of the industry. A strategic information system is a system that helps an organization gain a competitive advantage through its contribution to the organization's strategic objectives and/or the ability to significantly improve performance and productivity. Keywords: Information systems, IS/IT, Internal, External, Strategy